Empowering Rural Economies through BUMDes Initiatives in Indonesia - Indah Munfaati; Ilmi Usrotin Choiriyah (Indonesian Journal of Cultural and Community Development, 2024)
This qualitative study investigates the economic empowerment efforts through the "BUMDes Makmur Sejahtera" program in Pagerwojo Village, Buduran District, Indonesia, aligning with governmental regulations on village-owned enterprises. Using purposive sampling, data was collected via observation, interviews, and documentation. The analysis, guided by Miles & Huberman's model, highlights successful planning and policy adherence, community engagement through social and political actions, and the impact of awareness and education in enhancing local economic resilience. Key findings emphasize the need for improved marketing strategies and service quality to sustain and expand the program's benefits, positioning BUMDes as a pivotal tool for inclusive economic growth in rural communities, contingent on ongoing management and development efforts. Highlights: Strategic planning vital for BUMDes success in rural economic empowerment. Community engagement fosters effective governance and program sustainability. Education and awareness crucial for enhancing local economic resilience and growth. Keywords: BUMDes, economic empowerment, rural development, community engagement, qualitative research